ECONOMICAL DAMAGE OF THE RED wasp Vespa orientalis AND YELLOW WASP Polistes olivaceus ON GRAPES - AL-MAHDAWI, QASIM H.; AL-KINANI, MOHAMMED A. (Diyala Agricultural Sciences Journal, 2011)
The Red Wasp Vespa orientalis and yellow wasp Polistes olivaceus are hymenoptera insects present in our environment during spring and summer season. Their occurrence increase dramatically during the months of July, August and September. These wasps are found in orchards where attach grapes, figs, date and peach. they cause severe damage on both qualities and qualities of fruits. The adults of wasp chew on fruits causing severe injuries that may result in bacterial and fungal infections. In order to determine the damage caused by red and yellow wasps on grape, three grape varieties were selected: French, Kamalie and Halawani which are the most common varieties in consumer markets. The result of these experiments showed that the French variety was the most damage by wasps attack and the loss of weight was 108 % gm ⁄ cluster. The Al-Halawani was moderately elected with a loss of 71.7 gm ⁄ cluster and Al Kamali was the least with 40.0 gm ⁄ cluster of weight loss. The average attractiveness of wasps toward Al Halawani was 27.5 % and 72.4% for the red and yellow wasps respectively. However the red wasp attracted largely to the Al Kamaly variety with a 94.2 % where the yellow wasp attracted to French variety with a 89.5%. We found that the yellow wasp has an important role in damaging grape cluster of the all variety with a percent of 62.9% while the percent of red wasp was 37.1%. The difference of attractiveness between red and yellow wasps may be due to variety preference between wasps. It seems that the wasps have large role in economic loss of grape in addition to quality effect and lowering price of commodity.